Supplier selection decision support model: a case study of giant hypermarket in Selangor / Raja Nazim Raja Abdullah (Institute of Graduate Studies, UiTM, 2016)
Increased global competitiveness in supply chain foresees the significance of supplier selection with radical changes in decision-making process. Uncertain situation in purchasing, such as supplier selection, makes hypermarket relies on multiple criteria to make decision. Recent approaches of supplier selection implemented by hypermarket are still practicing a traditional decision-making process, using experience and personal judgment to decide on the supplier. Conflict of interest occurred when personal history is influenced by individual decision by decision makers. Hence, there are four types of multi criteria decision-making (MCDM) methods to solve decision problem and one of the decision models under MCDM is analytical hierarchy process (AHP), developed by Saaty (1980), is a tool for decision-making process continuously be the extensively decision-making theory to be employed. AHP has been widely exercised in solving decision problems. However, AHP tools are still lacking in performance and there are issues regarding supplier selection decision-making have been identified. This study introduced a multidisciplinary approach to operational decision support model applied to Giant hypermarket to provide the decision maker with a systematic decision making process…